2020
DOI: 10.3389/fcimb.2020.572909
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibiotic-Resistance by MALDI-TOF Mass Spectrometry: An Expanding Area

Abstract: Several MALDI-TOF MS-based methods have been proposed for rapid detection of antimicrobial resistance. The most widely studied methods include assessment of β-lactamase activity by visualizing the hydrolysis of the β-lactam ring, detection of biomarkers responsible for or correlated with drug-resistance/non-susceptibility, and the comparison of proteomic profiles of bacteria incubated with or without antimicrobial drugs. Antimicrobial-resistance to a number of antibiotics belonging to different classes has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…In our study, the major mass spectral intensity change was clearly seen after 6 h incubation with FLC. As reported by Vatanshenassan using MBT ASTRA prototype software, the discrimination between resistant and susceptible strains was accurately detected in 6 h [14]. Furthermore, the previous report explained that prolonged exposures antifungal drug in some isolates were allowed to increasing correctly identifying between S and R strains [8].…”
Section: Discussionmentioning
confidence: 60%
“…In our study, the major mass spectral intensity change was clearly seen after 6 h incubation with FLC. As reported by Vatanshenassan using MBT ASTRA prototype software, the discrimination between resistant and susceptible strains was accurately detected in 6 h [14]. Furthermore, the previous report explained that prolonged exposures antifungal drug in some isolates were allowed to increasing correctly identifying between S and R strains [8].…”
Section: Discussionmentioning
confidence: 60%
“…Apart from direct pathogen identification, the potential of MALDI-TOF MS for antimicrobial susceptibility testing has also been explored [ 23 ]. Johansson et al applied MALDI-TOF MS to screen for cfiA -positive B. fragilis strains directly from blood culture bottles with various ertapenem minimum inhibitory concentrations, yielding results within 3 h [ 90 ].…”
Section: Accuracy For Microbial Identification and Other Applicationmentioning
confidence: 99%
“…MALDI-TOF MS plays an important role in the identification of viruses, including influenza viruses, hepatitis viruses, and herpesviruses [ 16 , 17 , 18 , 19 ]. New studies have shown remarkable progress in the detection of microorganisms by MALDI-TOF MS and the identification of drug-resistant strains [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, Matrix-Assisted Desorption/Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) is catching on as a valid support in the workflow for laboratory diagnosis in clinical microbiology, especially for bacteriological identification [ 21 ] and virology [ 25 , 26 ]. More recently, thanks to its rapidity, accuracy and moderate price, MALDI-TOF MS has been employed as an alternative in the detection of antibiotic susceptibility/resistance biomarkers [ 27 , 28 ], in the identification of aminoacidic sequences and chemical structure of protein terminal groups [ 29 ], and as an emerging method in microbial typing [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%